2018
DOI: 10.3382/ps/pex332
|View full text |Cite
|
Sign up to set email alerts
|

Differences in intestinal size, structure, and function contributing to feed efficiency in broiler chickens reared at geographically distant locations

Abstract: The contribution of the intestinal tract to differences in residual feed intake (RFI) has been inconclusively studied in chickens so far. It is also not clear if RFI-related differences in intestinal function are similar in chickens raised in different environments. The objective was to investigate differences in nutrient retention, visceral organ size, intestinal morphology, jejunal permeability and expression of genes related to barrier function, and innate immune response in chickens of diverging RFI raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 39 publications
3
45
1
Order By: Relevance
“…However, the blend of organic acids and botanicals used in the current study, produced an increase in diversity and evenness for the jejunum compared to the ileum. Similarly, in other pharmacological studies, the biotransformation of drugs by the microbiota results in their absorption in the jejunum and are linked to increased diversity and biological activity of the microbial population [41,42]. The jejunum is the main sight for nutrient absorption in poultry [38], as well as in mammals, and it has been suggested that the jejunum is the most logical site to observe treatment effects [13] which is what we observed in the current study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the blend of organic acids and botanicals used in the current study, produced an increase in diversity and evenness for the jejunum compared to the ileum. Similarly, in other pharmacological studies, the biotransformation of drugs by the microbiota results in their absorption in the jejunum and are linked to increased diversity and biological activity of the microbial population [41,42]. The jejunum is the main sight for nutrient absorption in poultry [38], as well as in mammals, and it has been suggested that the jejunum is the most logical site to observe treatment effects [13] which is what we observed in the current study.…”
Section: Discussionsupporting
confidence: 78%
“…Though not considered in those earlier studies, it is possible that changes to the GIT microbial populations while the bird is developing could have contributed to the observed decreases in Salmonella and Campylobacter colonization, but additional studies are required to con rm this hypothesis. Studies support there is compartmental activation of the microbiota; but ultimately it will be the resulting physiological effects within the different compartments as they carry out their speci c biological processes [42,52] that will have the greatest impact. While feed e ciency, nutrient absorption, enzymatic activity and other GIT health indicators were not measured in this study, future studies will determine if these parameters are directly impacted by the microbial population in each compartment of the GIT.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous microbiota studies have focused on the ceca, which may not be ideal as digestion also occurs in the foregut [18,19]. Evidence suggests that the jejunum of feed-efficient animals, which is the site of nutrient absorption, has improved morphology, and increased enzymatic activity [20]. Likewise, the ileum, which absorbs any remaining vitamins and other nutrients not absorbed in the jejunum, is lighter and longer in more feed-efficient animals, with improved morphology [20].…”
mentioning
confidence: 99%
“…Evidence suggests that the jejunum of feed-efficient animals, which is the site of nutrient absorption, has improved morphology, and increased enzymatic activity [20]. Likewise, the ileum, which absorbs any remaining vitamins and other nutrients not absorbed in the jejunum, is lighter and longer in more feed-efficient animals, with improved morphology [20]. While the ceca are heavily focused on in other studies with natural compounds and for the microbiota responses, it may not necessarily be the site biological activity occurs nor the site with the most biological ramifications if the microbial populations change [16,17,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation